Goats under household conditions - Lebbie, S.H.B. (Elsevier, 2004)
Goats account for about 30% of Africa's ruminant livestock and produce about 17 and 12% of its meat and milk, respectively. Sub-Saharan Africa (SSA) accounts for over 60% of the total goat population in Africa, with an estimated 147million goats representing about 80 indigenous breeds or strains distributed across all agro-ecological zones and ruminant livestock production systems. Goats are particularly important in marginal agricultural land areas, especially in arid and semi-arid areas, which together hold 64% of the goat population. At the rural community level, goats play a significant role in the food chain and overall livelihoods of the poor rural households where they are also largely the property of resource poor women and their children. Indigenous goat breeds/strains are adapted to the diverse local production circumstances and are able to thrive with minimum inputs. Goats still remain largely marginalized, even at the household level. This paper attempts to look at the challenges and opportunities of goat keeping at the household level for the improved welfare of the keepers, using SSA as a representative of other developing sub-regions.